LEVEL OF ACTIVITY STUDENTS INTELLECTUAL DISABILITY IN PARTICIPATING PHYSICAL EDUCATION LEARNING: A Systematic Literature Review - Rahmadayanti, Resty Sriayu; Rohmah, Oom; Rahmat, Alit (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
Activeness is part of the physical education learning objectives that must be achieved. What is meant by activeness is a child who is actively moving. The aim of this research is to find out the level of activity of students with intellectual disabilities in participating in physical learning. This research was guided by PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) using the Google Scholar database. Based on 4 selected articles, this research identified the survey level of activity of students with intellectual disabilities in physical education learning. In the articles that have been reviewed, the first article conducted research at the Extraordinary Primary School, the second article conducted research at the Jombang State Special School, the third article conducted research at the C Tunas Harapan Karawang Extraordinary Junior High School, and the last article conducted research at the School. Extraordinarily Trustworthy. The method used in the four articles is a survey method with data collection using interviews, observation and document collection. After identifying the level of activity of mentally retarded students, it can be said to be active. Based on the research results and conclusions, recommendations are directed to future researchers to also conduct research on factors inhibiting the activeness of mentally retarded students in participating in physical education lessons.